The Effect of Work Ethics on Employee Performance at the Kampung Lalang Village Office - Karina Sri Ulina Br. Keliat; Putri Shandra Napitupulu; Shintia H.R Simanjuntak; Hasyim (Indonesian Journal of Advanced Research, 2023)
This study aims to determine the effect of ethics on the performance of employees in the Kampung Lalang Village Office. In this study, the samples were employees who worked at the Kampung Lalang Village Office. The data in this study were obtained by filling out a questionnaire. The research results say that there is a significant relationship between ethics in improving the performance of employees in the office.